pub fn to_sentence_case(non_sentence_case_string: &str) -> String
Expand description

Converts a &str to Sentence case String

    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "Foo bar";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);
    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "FooBar";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);
    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "fooBar";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);
    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "FOO_BAR";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);
    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "foo_bar";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);
    use cruet::cases::sentencecase::to_sentence_case;
    let mock_string: &str = "foo-bar";
    let expected_string: String = "Foo bar".to_string();
    let asserted_string: String = to_sentence_case(mock_string);
    assert!(asserted_string == expected_string);